Ultrabroadband MoS2 Photodetector with Spectral Response from 445 to 2717 nm. Issue 17 (23rd February 2017) - Xie, Ying; Zhang, Bo; Wang, Shuxian; Wang, Dong; Wang, Aizhu; Wang, Zeyan; Yu, Haohai; Zhang, Huaijin; Chen, Yanxue; Zhao, Mingwen; Huang, Baibiao; Mei, Liangmo; et al.
Abstract : Photodetectors with excellent detecting properties over a broad spectral range have advantages for the application in many optoelectronic devices. Introducing imperfections to the atomic lattices in semiconductors is a significant way for tuning the bandgap and achieving broadband response, but the imperfection may renovate their intrinsic properties far from the desire. Here, by controlling the deviation from the perfection of the atomic lattice, ultrabroadband multilayer MoS2 photodetectors are originally designed and realized with the detection range over 2000 nm from 445 nm (blue) to 2717 nm (mid‐infrared). Associated with the narrow but nonzero bandgap and large photoresponsivity, the optimized deviation from the perfection of MoS2 samples is theoretically found and experimentally achieved aiming at the ultrabroadband photoresponse. By the photodetection characterization, the responsivity and detectivity of the present photodetectors are investigated in the wavelength range from 445 to 2717 nm with the maximum values of 50.7 mA W −1 and 1.55 × 10 9 Jones, respectively, which represent the most broadband MoS2 photodetectors. Based on the easy manipulation, low cost, large scale, and broadband photoresponse, this present detector has significant potential for the applications in optoelectronics and electronics in the future. Abstract : Ultrabroadband multilayer MoS2 photodetectors with the optical response up to 4.7 µm are designed and realized . Their detection properties, ranging from 445 nm (blue) to 2717 nm (mid‐infrared), are investigated at room temperature by controlling the S defects, which show the broadest detecting range with low‐cost fabrication process and have potential applications in many optoelectronic devices.